The civil liability of electricity companies for the damage of electric poles in Jordanian legislation compared to Islamic jurisprudence - Al- Doum, Rad Talal (Journal of Economic, Administrative and Legal Sciences, 2019)
This message came to find sound foundations for the purpose of reducing the danger of electric poles, and to clarify the legal centers in the legal obligations placed upon each of the electricity companies and subscribers and others in order to prevent the danger of electric poles. The study reached a number of results, the most important of which is the absence of legislative clearness in the General Electricity Law No. 64 of 2002, where the law did not deal adequately and accurately with the mechanism of prevention of the danger of electric columns, including the explicit procedures to be taken by electricity companies in order to reduce the risk resulting from The electric columns through the establishment of quick and sound procedures that achieve the highest desired goal of protecting the human lives. The study also concluded with a number of recommendations, the most important of which is the assignment of these companies to monitor and inspect periodically by patrols their lines and electrical columns. Article 3 of the Electricity Allowance issued under the General Electricity Law No. 64 of 2002 must be amended to achieve the desired goal, which is to prevent the danger of electric columns and to oblige the electricity companies to change the pare electrical lines, with other insulated to protect against the danger caused by the electric columns, in addition to the approach of dispensing On the electric columns through the extension of electrical cables within trenches that have good specifications to achieve public safety, and the creation of awareness campaigns, in turn, to educate media about the danger that result from the electric columns and the mechanism of dealing with these facilities And the columns in the natural and extraordinary circumstances during the occurrence of the fall of a column or the interruption of a cable, and these campaigns must be targeted specifically at the children, and as conclusion by the activation of the rule of jurisprudence, the most severe damage is replaced by the slightest damage "because this role has the positive impact on the preservation of life and property From Severity caused by electric columns.